COVID-19 Survey Participation and Wellbeing: A Survey Experiment. (July 2021) - Sollis, Kate; Biddle, Nicholas; Edwards, Ben; Herz, Diane
Individuals throughout the world are being recruited into studies to examine the social impacts of coronavirus disease 2019 (COVID-19). While previous literature has illustrated how research participation can impact distress and wellbeing, to the authors' best knowledge no study has examined this in the COVID-19 context. Using an innovative approach, this study analyses the impacts of participation in a COVID-19 survey in Australia on subjective wellbeing through a survey experiment. At a population level, we find no evidence that participation impacts subjective wellbeing. However, this may not hold for those with mental health concerns and those living in financial insecurity. These findings provide the research community with a deeper understanding of the potential wellbeing impacts from COVID-19-related research participation.